SUPERVISI PENDIDIKAN SEBAGAI UPAYA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH - Fortunately, Renil; Sriwahyuni, Eci (UIN Imam Bonjol Padang, 2024)
Educational supervision plays a crucial role in efforts to improve the quality of education in schools. Through educational supervision, various initiatives to enhance and improve the learning process can be undertaken. This study employs a systematic literature review (SLR) method consisting of six stages: planning, literature search, criteria assessment (inclusion and exclusion), quality assessment, data collection, and data analysis. The study aims to determine the role of supervision in improving educational quality, the strategies for implementing educational supervision, and the challenges faced in its application. Data analysis results indicate that educational supervision plays a central role in enhancing educational quality by identifying strengths and weaknesses in teaching practices, providing constructive feedback to educators, and promoting professional development. Strategies used in educational supervision include direct observation, counseling or mentoring, peer coaching or collaboration among educators, and document or portfolio review. Challenges in implementing educational supervision include time constraints, ineffective communication skills of supervisors, and teachers' resistance to supervision due to discomfort.